Educating learning technology designers : guiding and inspiring creators of innovative educational tools - Chorost, Michael; DiGiano, Chris; Goldman, Shelley V. (Routledge, 2009)
What knowledge and skills do designers of learning technologies need? What is the best way to train them to create high-quality educational technologies? Distilling the wisdom of expert instructors and designers, this cutting-edge guide offers a clear, accessible balance of theory and practical examples. This cutting-edge guide: synthesizes learning, instructional design, and educational technology perspectives on learning-centered technology - highlighting how interdisciplinary work is driving the fields of the learning sciences and technology design and development
Keywords: Educational technology; Computer-assisted instruction